2022
DOI: 10.21037/qims-21-706
|View full text |Cite
|
Sign up to set email alerts
|

Identifying 18F-FDG PET-metabolic radiomic signature for lung adenocarcinoma prognosis via the leveraging of prognostic transcriptomic module

Abstract: Background: Imaging with 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET), which identifies molecular and metabolic abnormalities within tumor cells, could support prognostic assessment of lung adenocarcinoma (LUAD). We aimed to develop a radiomic signature with the aid of a transcriptomic module for individualized clinical prognostic assessment of LUAD patients.Methods: Using a gene expression profile consisting of 334 stage I-IIIA LUAD patients, prognosticrelated gene coexpression modules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Moreover, functional analyses revealed that these DEGs were linked to lung cancer tumorigenesis and metastasis. The most significantly enriched pathway, the cell cycle signaling pathway, has been shown to have mutations that can affect the genomic and microenvironmental characteristics of LUAD patients 36 and can also be used as an assessment criterion for post-operative adjunctive therapy in LUAD patients 37 . Furthermore, GSEA analysis revealed that these DEGs might affect base excision repair, the cell cycle, DNA replication, mismatch repair, and the p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, functional analyses revealed that these DEGs were linked to lung cancer tumorigenesis and metastasis. The most significantly enriched pathway, the cell cycle signaling pathway, has been shown to have mutations that can affect the genomic and microenvironmental characteristics of LUAD patients 36 and can also be used as an assessment criterion for post-operative adjunctive therapy in LUAD patients 37 . Furthermore, GSEA analysis revealed that these DEGs might affect base excision repair, the cell cycle, DNA replication, mismatch repair, and the p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%